Postmodern malpractice a medical case study in the culture war - Clements, Colleen D. (Oxford ; New York : JAI, 2001)
In this work, Colleen Clements presents her case for the need to subject the field of bioethics to a critical external analysis apart from the current postmodern assumptions. Clements argues that, since the 1970s, bioethics has refuted human values in favour of political consensus building. This failure to recognize basic human values in the ethical critique of modern medicine has lead to a dehumanization of the medical system by the field. Clements proceeds to advocate a naturalistic theory of bioethics that reinstates primary human values.
Introduction: the Trojan horse of bioethics -- What really assassinated Hippocrates -- Bioethics in historical and philosophical context -- The postmodern environment of bioethics -- Human reproductive medicine: freedom or regulation -- Infectious diseases: ethics, experts and policy in AIDS, vCJD, Ebola virus, West Nile virus -- Abortion: human worth, the end of ethics and political entitlement -- Politicizing brain death, treatment refusal, physician-assisted suicide, terminal sedation, treatment rationing -- Health belief model and health delivery systems -- Alternative medicine, new age, classic shaman systems -- Behavioral myth, psychiatric abuse, and social manipulation -- Are patients better off than they were before the sixties: a second opinion and analysis of bioethics -- Resisting the total society, and a new model for ethics.
Includes bibliographical references.
Description based on print version record.
Keywords: Medical ethics -- Case studies; Medical ethics -- Social aspects -- Case studies; Bioethics -- Case studies; Social ethics -- Case studies; Bio-ethics.; Medical -- Ethics